(untitled) (Global Journal of Management and Business Research, 2019)
The main objective of this study was to establish the effect of business mergers on employee loyalty in selected companies listed at the Nairobi Securities Exchange Descriptive research design was used in this study The target population of the study comprised of employees in the management level of three companies listed at the Nairobi securities Exchange that embraced mergers between the years of 2002 -2011 The sample consisted of top level managers middle level managers and lower level managers in different departments Data was collected using questionnaire Both stratified and random sampling was used to obtain a sample size of 54 out of a target population of 308 respondents Data was analyzed using descriptive statistics and the findings were presented using tables charts and figures The study found out that organization culture affect the employees and also culture differences affects employees loyalty More so if the management involved the employees in the merger process the process would be successful and the way the informationabout merger is communicated to the employees is very impotant